Digital Marketing Strategy to Improve Sales Performance of Turkey Shawarma Restaurant in East Jakarta : A SWOT and BCG-Based Approach - MOHAMMED, LUAY ABDULLAH ABDULLAH (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
Abstract. This study examines how online marketing strategies can maximize the sales performance of Turkey Shawarma Restaurant in East Jakarta. The study employs SWOT analysis and the BCG Matrix to identify strategic positioning, internal strength of original recipes and location advantage, and weaknesses of low online presence. It also identifies external opportunities such as growth in online food ordering and adoption of e-wallets and threats such as increased competition. The study recommends a digital transformation approach entailing social media campaigns, search engine optimisation, and partnerships with online food delivery platforms. Results show that adoption of digital tools can result in significant brand visibility and customer engagement. The proposed strategy is aligned with Sustainable Development Goals (SDG), namely inclusive economic growth and innovation. Online platform integration should grow sales by 25-30% in 6-9 months and place the restaurant on solid ground in Jakarta’s F&B market. Keywords: Digital Marketing, SWOT Analysis, BCG Matrix, Food Business, MSMEs, Sustainable Development, SDGs.